P6 Intervention monitoring in maternity and paediatrics as a strategy to guide education and improve prescribing practice. Issue 2 (19th January 2018) - Tweedie, Kelly; Haley, Helen
Abstract : Aim: This audit explores the impact of regular pharmacist intervention monitoring and feedback on paediatric and maternity wards, and how these interventions guide educational strategies aimed at improving prescribing practice. Method: A tally-chart data collection tool was designed for each ward to collect data on common errors such as omission of booking weight, vital to ensure safer prescribing of dalteparin, omission of dose/kg imperative to ensure safer paediatric prescribing, and also omission of the residing ward from the front of the chart which affects discharge times when TTOs are delayed/lost due to misdirection. The ward pharmacist recorded the incidence of these errors during each daily visit and prepared a weekly feedback report consisting of a bar graph of the results plus a comparison to the previous week. The pharmacist would also reiterate the importance of avoiding each type of error. This would also inform the topic of the 'key prescribing message' (a bulletin focussing on a particular type of error) explaining the correct method and the significance of avoiding errors. This was communicated to the ward teams/prescribers. Results: Preliminary audit data is encouraging and shows that the feedback to the ward teams has had a positive impact. Many nurses and midwives were surprised at the level of errors and now better understand their significance and how they can support accurate prescribing. The senior medics have taken an interest in the audit and are keen on sharing the information with their juniors and adapting their training to ensure that further improvements are made. The data collected informed the first 'key prescribing messages'; 'Booking weight' for maternity and 'medicines reconciliation' for paediatrics. Since these were communicated to the ward teams/prescribers the audit has found an improvement in the number of maternity prescriptions with the booking weight recorded, a reduction in the number of incorrect dalteparin prescriptions for postnatal women, as well as improved prescribing practice in paediatrics such as including dose/kg on each prescription and improved drug-history taking by the medics. Conclusion: A key priority of the NHS is the prevention of medication errors. 1 The positive impact of clinical pharmacist interventions on the quality of prescribing is well established 2, 3 as highlighted in a Department of Health study 4 reviewing the frequency of errors, identifying modes of good practice to improve safety. To date this audit has shown the benefit of increasing the multidisciplinary team awareness of common errors, monitoring these each week and sharing these findings with the team. It has also shown that short, focused bulletins encouraged improvement and helped prescribers to improve their practice. References: Audit Commission. A spoonful of sugar-improving medicines management in NHS hospitals 2001. London: Audit Commission. Dale A, Copeland R, Barton R. Prescribing errors on medical wards and the impact of clinical pharmacists. Int J Pharm Pract2003;11:19–24. Dhillon S. Do clinical pharmacists really improve the quality of patient care? Hospital Pharmacist 2001;8:118. Department of Health. Building a safer NHS for patients . Improving medication safety 2004. London: Stationery Office.